2020
DOI: 10.3389/fnins.2020.562035
|View full text |Cite
|
Sign up to set email alerts
|

Total Sleep Deprivation Impairs Lateralization of Spatial Working Memory in Young Men

Abstract: Total sleep deprivation (TSD) negatively affects cognitive function. Previous research has focused on individual variation in cognitive function following TSD, but we know less about how TSD influences the lateralization of spatial working memory. This study used event-related-potential techniques to explore asymmetry in spatial-working-memory impairment. Fourteen healthy male participants performed a two-back task with electroencephalogram (EEG) recordings conducted at baseline and after 36 h of TSD. We selec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 67 publications
2
8
0
Order By: Relevance
“…Importantly, limited evidence has also suggested that SD disrupts hippocampus-dependent spatial memory in humans ( Ferrara et al., 2008 ; Peng et al., 2020 ). Moreover, clinical observations have documented that patients who suffer from a clinical sleep disorder often exhibit spatial memory deficits.…”
Section: Sleep Disturbance and Spatial Memorymentioning
confidence: 99%
“…Importantly, limited evidence has also suggested that SD disrupts hippocampus-dependent spatial memory in humans ( Ferrara et al., 2008 ; Peng et al., 2020 ). Moreover, clinical observations have documented that patients who suffer from a clinical sleep disorder often exhibit spatial memory deficits.…”
Section: Sleep Disturbance and Spatial Memorymentioning
confidence: 99%
“…The P3 amplitude increased with task difficulty and was larger in table tennis players than in the controls. The P3 component reflects the deployment of attentional resources, and the P3 amplitude reflects an individual’s ability to distinguish and evaluate target stimuli [ 19 ]. Long-term special training can help table tennis players actively adapt to fast, complex, and changeable situations.…”
Section: Discussionmentioning
confidence: 99%
“…P300 (also termed P3) is affected by the objective probability of an event and the subjective expectation before the stimulus occurs. It is a sign of stimulus evaluation, attention capacity, processing time, and content update [ 19 ], reflecting the deployment of attention resources.…”
Section: Introductionmentioning
confidence: 99%
“…[ 8 , 9 ] Working memory is an important component of cognitive neuroscience research [ 10 , 11 ] and includes form-specific information storage systems comprising a phonological loop that processes verbal information, a visuospatial sketchpad for processing spatial information, and a central executive system consisting of 3 cognitive processes (inhibition, shifting, and updating). [ 12 ] Peng [ 13 ] in their study found that sleep insufficiency impaired the working memory ability of college students.…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that exposure to high altitudes can easily lead to sleep insufficiency, [ 6 ] which can impair individual working memory. [ 13 ] However, individuals may have different sleep performances and processing patterns of spatial working memory in low-pressure and hypoxic environments. Therefore, we decided to use the spatial 2-back paradigm and combined ERP technology with it to investigate the effects of sleep insufficiency on spatial working memory under low-pressure and low-oxygen environments.…”
Section: Introductionmentioning
confidence: 99%